Outcomes of Non-Operative Management Versus Early Surgery in Patients with Uncomplicated Appendicitis: A Prospective Comparative Study - Khan, Abdullah; Khan, Muhammad Iqbal; Mahmood, Maria; Arbab, Riffat; Arshad, Aisha; Anwar, Rukhsar (Biological and Clinical Sciences Research Journal, 2025)
The optimal management of uncomplicated appendicitis remains debated, with increasing interest in non-operative management (NOM) as an alternative to early surgery. Objective: This study compares clinical outcomes of NOM versus early surgical intervention in patients with imaging-confirmed uncomplicated appendicitis. Methods: This prospective comparative study was conducted at Bolan Medical College, Quetta, from July 2024 to December 2024. Ninety-five patients aged 15–60 years with ultrasonography or computed tomography-confirmed uncomplicated appendicitis were included. Patients were allocated to NOM (n = 47; intravenous ceftriaxone and metronidazole followed by oral antibiotics) or early surgery (n = 48; laparoscopic appendectomy within 24 hours). Results: Primary treatment success was achieved in 89.4% of NOM patients versus 100% of surgical patients (p = 0.026). Recurrence within six months occurred in 16.7% of NOM patients, whereas no recurrences were observed in the surgical group (p = 0.003). Complications during index admission were significantly lower in the NOM group (6.4% vs 18.8%, p = 0.049). Mean hospital stay was shorter for NOM (2.1 ± 0.9 days) compared to surgery (3.4 ± 1.2 days, p < 0.001). Readmission rates did not differ significantly (10.6% vs 4.2%, p = 0.21). Conclusion: Non-operative management is a safe and effective initial strategy for selected patients with uncomplicated appendicitis, offering fewer short-term complications and reduced hospitalisation. However, the risk of recurrence remains an important consideration.